Perda Berbasis Syari’ah dan Hubungan Negara-Agama dalam Perspektif Pancasila - Na'imah, Hayatun; Mardhiah, Bahjatul (Mazahib, 2016)
Presidential Decree 1959 declared that the state of Indonesia back to the Constitution of 1945. The preamble of the 1945 Constitution turned out to comprise the formulation of article 1 of Pancasila which states the obligation of adherents of Islam to comply with Islamic law (a.k.a. the Jakarta Charter). Presidential Decree 1959 cannot nominally be used as the basis for the enactment of Shari'a in Indonesia as a whole. Even so, it has provided a place for the position of Shari'a in Indonesia, or at least been a foundation for the establishment of national legislation that is based on Shari'a. This article discusses the justifiability of Shari’a bylaws by means of the socio-historical value of the first principle of the Pancasila which is accommodative to Shari`a. It argues that Pancasila cannot only be viewed in terms of legal ideals containing philosophy as well as the idea of ideas and cultural values of a nation, but also the reflection of the moral values of Islam in all aspects of human life as a whole. Therefore, the existence of Sharia bylaws can be justified from the standpoint of the first principle of the Pancasila.